Differential methylation between sex in adult green sea turtle skin biopsies - Mayne, Benjamin; Mustin, Walter; Baboolal, Vandanaa; Casella, Francesca; Ballorain, Katia; Barret, Mathieu; Vanderklift, Mathew A.; Tucker, Anton D.; Berry, Oliver (Frontiers in Marine Science, 2023)
In marine turtles, sex is determined by egg incubation temperature. This places marine turtle species at risk from global warming as this may skew hatchling towards one sex. Assessment of this risk at the population level requires sex identification of turtle hatchlings. However, available methods are either, lethal, highly invasive, and difficult to conduct at a large scale. DNA methylation, an epigenetic modification, has been shown to be a biomarker for environmentally determined sex in many species. In this study, we sought to develop a rapid, minimally invasive, and inexpensive method to identify the sex of marine turtles. We used reduced representation bisulfite sequencing DNA methylation data from adult green sea turtle (Chelonia mydas) skin biopsies to identify 16 differentially methylated genomic regions between males and females (adjusted p-value < 0.01). We designed methylation sensitive qPCR assays for these regions and tested their capacity to identify the sex of turtles ranging in age between 3-34 years. The qPCR assay identified the sex in turtles > 17 years with high accuracy. However, the sex of younger turtles could not be accurately identified. This suggests the sex differences distinguishable by the assay were adult specific, reflecting the training data on which the sex-specific regions were identified, and likely linked to late-stage ontogenetic changes associated with sexual maturity. Future research into sex-specific differentially methylated regions in hatchlings and juveniles should be based on genome-wide DNA methylation data from a wider age range.